Task performance, task importance, and educational needs for novice-level nursing tasks as perceived by neonatal intensive care unit nurses with various levels of experience in South Korea: a cross-sectional study. - Ha, You La; Cho, Hun Ha (Child Health Nursing Research, 2026)
Purpose: This study aimed to identify differences in perceived task performance, task importance, and educational needs for novice-level tasks among neonatal intensive care unit (NICU) nurses with varying levels of clinical experience and to provide foundational data for developing systematic educational programs to strengthen the competencies of novice nurses. Methods: Participants were recruited from the NICUs of three hospitals--one university-affiliated hospital and two general hospitals located in Busan, South Korea. Using convenience sampling, 116 staff nurses with at least 3 months of NICU experience were surveyed between March and November 2025. For comparative analysis, participants were divided into three career groups based on their NICU experience: <3 years, 3-9 years, and ≥9 years. Data were analyzed using descriptive statistics, analysis of variance, and the Scheffé test with IBM SPSS ver. 25.0, and importance--performance analysis (IPA) was conducted to prioritize educational needs. Results: Across all career groups, the "direct nursing performance" domain showed the highest task performance. Novice nurses with <3 years of experience reported significantly higher performance in central line care and transfusion management than those with ≥9 years of experience. The IPA identified central line management, and transfusion management as priority areas for improvement, while vital sign monitoring, respiratory surveillance and discharge education for parents were common educational needs regardless of experience level. Conclusion: Educational programs for novice NICU nurses should focus on strengthening patient safety--related competencies and should be progressively structured with simulation and case-based learning to enhance clinical performance.